Good intentions and the public good: Intangible cultural heritage in a Canadian national museum - Laforet, Andrea (Ethnologies, 2014)
For more than one hundred years Canada’s national museum of human history, called, successively, the National Museum of Canada, the National Museum of Man, the Canadian Museum of Civilization, and, most recently, the Canadian Museum of History, has documented and assembled a record of intangible cultural heritage relating to various cultural groups. Originally collected and currently preserved under legislative mandates resting on broad assumptions about the public interest, this material includes a substantial body of narrative, song and information relating to both past and contemporary cultural practice of societies indigenous to Canada. This paper explores the issues for concepts of nationhood, knowledge and the public interest raised by the contractual agreements, legislation on topics ranging from copyright to family law, treaty negotiations between Aboriginal people and the Government of Canada, and consultation concerning different cultural definitions of property and the sacred that affect day-to-day access to and use of Aboriginal intangible heritage in the museum. Finally, the paper explores potential issues for the continuation of this work raised by the museum’s narrowing of focus and mandate as it changes from the Canadian Museum of Civilization to the Canadian Museum of History.